Hypersensitivity and Cardiovascular Risks Related to Allopurinol and Febuxostat Therapy in Asians: A Population‐Based Cohort Study and Meta‐Analysis. Issue 2 (20th March 2019) - Chen, Chi‐Hua; Chen, Chun‐Bing; Chang, Chee Jen; Lin, Yu Jr; Wang, Chuang‐Wei; Chi, Ching‐Chi; Lu, Chun‐Wei; Chen, Wei‐Ti; Pan, Ren‐You; Su, Shih‐Chi; Hsu, Lung‐An; Chang, Ya‐Ching; et al.
Abstract : The safety of newer xanthine oxidase inhibitor febuxostat compared to allopurinol remains unclear. To compare the risks of allopurinol hypersensitivity and febuxostat hypersensitivity and cardiovascular diseases (CVDs) in Asians, we conducted a population‐based cohort study enrolling patients receiving allopurinol or febuxostat from Chang Gung Memorial Hospital Health System across Taiwan during 2012–2016 and further performed a meta‐analysis incorporating two recent studies. Among the 61, 539 users, a corresponding 12, 007 and 5, 680 patients were identified as new users. The overall incidence of febuxostat hypersensitivity was significantly lower than allopurinol hypersensitivity (0.2 vs. 2.7 per 1, 000 new users; P < 0.001). There were 33 allopurinol‐hypersensitivity reactions (including 18 severe cutaneous adverse drug reactions), and only one patient developed febuxostat‐maculopapular exanthema. Moreover, febuxostat did not statistically increase the risk of CVD (hazard ratio (HR), 1.16; P = 0.152) and related death (HR, 1.49; P = 0.496) compared to allopurinol. The result of the meta‐analysis also showed a consistent result. In conclusion, the incidence and severity of febuxostat‐hypersensitivity are lower than with allopurinol. Febuxostat did not show an increased risk of CVD and related death.